2009
DOI: 10.1128/jcm.00187-09
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization of Enterocytozoon bieneusi in Specimens from Pigs and Humans in a Pig Farm Community in Central Thailand

Abstract: We determined that 15.7% of pigs and 1.4% of humans in a pig farm community in central Thailand harbored Enterocytozoon bieneusi. Genotyping of E. bieneusi from pigs showed genotypes O, E, and H. However, only genotype A was found in human subjects. This indicates nonzoonotic transmission of E. bieneusi in this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
26
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 26 publications
10
26
3
Order By: Relevance
“…The finding of genotype O in pigs in the present and previous studies supports the potential for zoonotic transmission (24,26,28). Genotype O seems to have strict host specificity, as it is found only in pigs and humans.…”
Section: Enterocytozoon Bieneusi In Pigssupporting
confidence: 90%
See 3 more Smart Citations
“…The finding of genotype O in pigs in the present and previous studies supports the potential for zoonotic transmission (24,26,28). Genotype O seems to have strict host specificity, as it is found only in pigs and humans.…”
Section: Enterocytozoon Bieneusi In Pigssupporting
confidence: 90%
“…1). Among the six known genotypes identified in the present study, genotypes H and CS-1 have been found only in pigs (21,(25)(26)(27)29). In spite of this, the conclusion that pigs are a specific host of genotypes H and CS-1 cannot currently be drawn because of the lack of epidemiological data from human and animal microsporidiosis.…”
Section: Enterocytozoon Bieneusi In Pigscontrasting
confidence: 57%
See 2 more Smart Citations
“…Enterocytozoon bieneusi, the most frequently diagnosed microsporidial species in humans, was first reported in an AIDS patient in 1985 (4). Over the last 2 decades, E. bieneusi has been detected in humans, other mammals, and birds in more than 30 countries (1,6,10,12). However, the prevalence of this parasite in China has been unclear.…”
mentioning
confidence: 99%